Brodalumab in the Treatment of Plaque Psoriasis Localized in Difficult-to-Treat Areas: a Narrative Review - Cannizzaro, Maria Vittoria; Coscarella, Giulia; Chiricozzi, Andrea (Dermatology Practical & Conceptual, 2023)
Introduction: Psoriasis is a common chronic, immune-mediated, inflammatory skin disease that in certain localization results difficult to treat. Psoriatic lesions in difficult-to-treat areas might be hardly managed as no standardized therapeutic approach and the application of topical treatments might have marred limitations. Systemic agents, including biologic therapies, have been proven effective in treating this subgroup of patients. In particular, current evidence has shown beneficial effects with the use of brodalumab, a fully human IgG2 monoclonal antibody antagonizing the IL-17 receptor A subunit (IL-17RA). Objectives: The aim of this narrative review was to collect published data about efficacy and safety of brodalumab in the treatment of psoriasis occurring in difficult-to-treat areas. Methods: Data on brodalumab effectiveness and safety deriving from both trials and real-world setting that had been published in the last 15 years were collected for this review, together with clinical findings issued during international meetings. Results: In phase 3 trials, brodalumab demonstrated to be effective in promoting a rapid response in scalp psoriasis as well as in generalized pustular psoriasis and erythrodermic psoriasis. Nail psoriasis demonstrated marked clinical improvement after treatment with brodalumab. Amelioration of palmoplantar psoriasis was also described in brodalumab-treated patients. Various retrospective real-world studies reported a complete clearance of psoriatic lesions in difficult-to-treat areas, including genitalia, through short-term brodalumab treatment. Conclusions: Brodalumab, combining rapid and sustained efficacy with a favorable safety profile, may be a valid therapeutic option for severe variants of psoriasis as well as for psoriasis localized in difficult-to-treat areas.